The Alps, high gods, and the great flood: stone axe exchange and cosmology in Aboriginal south-eastern Australia – a response to Hiscock's 'Beyond the Dreamtime'. Issue 1 (4th May 2017) - Brumm, Adam
Abstract: There is historical evidence for the belief among Aboriginal communities of pre-colonial south-eastern Australia that the sky was in imminent danger of collapsing, and all of humanity perishing in an epic flood, unless stone axes were bestowed upon a powerful deity that dwelt in the Australian Alps. Previously, I have argued that this 'falling sky' story provides insight into the elaborate symbolism associated with stone axes in Aboriginal societies of the southeast, particularly with regards to cosmological dimensions of the vast axe trading network centred on the renowned Mount William quarry. Recently, however, Peter Hiscock (2013) has proposed that this entire incident is more parsimoniously interpreted as a response to the disruptions created by British colonisation, and hence, this notion of an impending apocalypse has no bearing on our understanding of the long distance exchange of stone axes in the pre-contact history of this region. Here, I provide a more detailed analysis of the falling sky story and its wider context in historically known Aboriginal societies of the southeast. I reject the argument proposed by Hiscock (2013) that the beliefs underpinning it contain Christian motifs. Aboriginal oral traditions from throughout the southeast refer to deity-induced floods that destroyed an 'antediluvian' world of humans and marked the beginning of a new cultural epoch. While these flood myths superficially resemble biblical notions of a world-ending deluge, I argue that they are probably oral histories of post-glacial sea-level rises, and thus, distinctly ancient. The falling sky story, I conclude, offers hints at the extent to which religious knowledge and symbolic belief were integrated with economic dimensions of the stone axe exchange system in south-eastern Australia.